Composition and connectivity variability of the A15 phase in PIT Nb3Sn wires. (20th July 2015) - Tarantini, C; Segal, C; Sung, Z H; Lee, P J; Oberli, L; Ballarino, A; Bottura, L; Larbalestier, D C
Abstract: Powder-in-tube (PIT) Nb3 Sn wires are competing with Restacked-Rod-Process (RRP ® ) for the realization of the high luminosity upgrade of the Large Hadron Collider (LHC) at CERN. These two conductors have different properties and microstructures that are in both cases averages of an inhomogeneous A15 microstructure. PIT has in general a smaller fraction of A15 in the non-Cu cross-section than RRP ® and a lower non-Cu J c (12 T, 4.2 K) (2500–2700 A mm −2 versus 2900–3000 A mm −2 ) but it can be made in smaller filament diameters, which is an important property for LHC magnets. Another characteristic of PIT A15 is that ∼25% is made up of ∼1–2 μ m sized grains (typically ∼10 times the small grain (SG) diameter) and their contribution to transport is uncertain. Here we studied a 192 filament Ta-doped, 1 mm diameter PIT wire and combined multiple characterization techniques in order to distinguish the different wire components, to determine their individual properties and to identify which components are current-carriers. We found multiple evidence that the large A15 grains, which are also the highest- T c grains, do not contribute to transport at high field and that the only current-carrying A15 is the SG with T c <17.7 K. However, because of the high density of grain boundaries in the SG A15 layer, PIT has an exceptionally high SG-layer J c and high specific grain boundary pinning force, Q GB . These findings clearly show that it is essential to increase the ratio of small to large and disconnected grains in order to improve PIT performance.